Modified Separator with Nitrogen‐doped High‐graphitized Carbon for Lithium‐sulfur Batteries. Issue 9 (12th April 2022) - Wei, Benben; Xia, Yu; Chen, Shaoqing; Wang, Hsing‐Lin
Abstract: Suppressing the shuttling of dissolved lithium polysulfides (LiPSs) is an indispensable strategy to extend the cycling life of lithium‐sulfur (Li−S) batteries. One strategy is absorbing the LiPSs by modifying separator of Li−S batteries. Herein, we show a novel nitrogen‐doped graphitized carbon (NGC) derived from coconut shell, which was annealed by flash Joule heating at ultrahigh temperature within seconds. The NGC was coated on the polypropylene (PP) separator to prepare the modified PP separator, which enabled the Li−S batteries to work stably at 1 C with a low fading rate of 0.09 % from 788 mAh g −1 . Microscopy analysis and Raman spectrum reveal that the high‐graphitization carbon with heavily nitrogen‐doping strengthens the adsorption of LiPSs in the charge/discharge process. Abstract :